Pengembangan Media Digital Berbantuan Kinemaster Materi Siklus Makhluk Hidup dan Upaya Pelestariannya Kelas IV SD - Santoso, Marizah Yulia; Sriwijayanti, Ribut Prastiwi; Jannah, Faridahtul (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2025)
This study was motivated by students' lack of understanding of the material, less active students and lack of student focus during learning. The use of media that relies on printed media, especially the material of the cycle of living things and efforts to preserve it in class IV. The purpose of this study is to develop digital media products assisted by kinemaster as a learning tool applied to IPAS lessons on the material of the cycle of living things and efforts to preserve it to make it easier for students to understand the material.  The method used is research and development (R&D), using steps from the ADDIE model that has been developed by Dick and Carry including Analyze, Design, Development, Implementation, Evaluation. The research subjects were 23 students of class IV A SDN Wiroborang 1.  The data instruments used are material expert validation sheets, media experts, learning practitioners and student responses. The results of the material expert validation research amounted to 84%, media experts 96%, learning practitioners 98% and student responses 84.5%. Based on the results of research and development of digital media assisted by kinemaster material cycle of living things and their conservation efforts in class IV, has been valid with an overall result of 90.6%. Therefore, this media is declared very feasible to use in learning activities at school. Thus, digital media assisted by kinemaster is expected to be developed again based on the needs of students and further research is needed to get optimal results.